Compressão adaptativa de arquivos HTML em ambientes de comunicação sem fio - Rainer Ronnie Pereira Couto (2003)
The increasing development of mobile computing technologies has allowed users to access the Internet any time and anywhere. However, as the resources of mobile devices are scarcer than their counterparts in wired network, there is the need to adapt data documents in order to provide efficient access to applications and services in wireless environments. In this work, it is proposed a model which predicts how and when a file should be compressed before its transmission over a wireless channel, aiming to minimize the impact on energy consumption and to improve response time. Experiments in real scenarios and simulations using ns2 simulator with both IEEE 802.11 and Bluetooth technologies prove the efficiency of this model when compared with other simplistic approaches adopted in literature